Bioatividade de espécies vegetais em relação a Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae: Bruchinae) em feijão (Phaseolus vulharis L. 1753) - Araújo, Alice Maria Nascimento de (2010)
The common bean Phaseolus vulgaris (Linnaeus, 1753) (Fabaceae) is a legume of great importance as a source of vegetal protein in Brazil. The insect damages bean grains and reduces its quality, affecting the appearance, palatability and acceptability by the consumers. The weevil Zabrotes subfasciatus (Boheman, 1833) (Coleoptera: Chrysomelidae: Bruchinae) is one of the main pests of stored beans. The larvae of this insect open galleries in the bean grains, attacking the cotyledons and can completely destroy them. The methods currently used to control storage pest species are the purges and treatment with residual insecticides that are not always effective to exterminate the pests or to prevent reinfestation, and may result in problems such as insect resistance and animals and humans poisoning. This work aimed to evaluate the insecticidal activity of ten different plant species for the control of Z. subfasciatus. The weevil repellence, mortality, oviposition and adult emergence were evaluated in a non-choice test and the weevil oviposition and adult emergence were evaluated in a free-choice test. The plant species used were: Anadenanthera colubrina (Vell.) (cebil), Annona muricata L (soursop), Azadirachta indica A. Juss. (neem), Caesalpinia pyramidalis Tul. ( catingueira ), Chenopodium ambrosioides L. (Mexican tea), Cymbopogon citratus Stapf. (lemongrass), Cymbopogon sp. (citronella), Momordica charantia L. (bitter melon), Ricinus communis L. (castor oil plant) and Piper nigrum L. (Black pepper). For the repellence evaluation, a repellence index was established, using the t test for comparing the means. For the mortality and oviposition analysis, in the non-choice test, the F test was used and, when necessary, the means were compared by the Tukey´s test. Mortality, oviposition and adult emergence data were verified and, through a regression analysis, it could be concluded that C. ambrosioides and P. nigrum powders were highly toxic to the weevils, both causing 100% mortality after only four days of exposure. The powders from A. muricata, A. indica, C. pyramidalis, C. ambrosioides, Cymbopogon sp., C. citratus and P. nigrum were repellent to Z. subfasciatus adults and, except for C. pyramidalis, they little prefered oviposition in the free-choice test. In the non-choice oviposition test, there were no eggs on beans treated with C. ambrosioides and P. nigrum powders, and consequently, there was no adult emergence.